2013
DOI: 10.28945/1887
|View full text |Cite
|
Sign up to set email alerts
|

The Wheels on the Bot go Round and Round: Robotics Curriculum in Pre-Kindergarten

Abstract: Executive SummaryThis paper qualitatively examines the implementation of an intensive weeklong robotics curriculum in three Pre-Kindergarten classrooms (N=37) at an early childhood STEM (science, technology, engineering, and math) focused magnet school in the Harlem area of New York City. Children at the school spent one week participating in computer programming activities using a developmentally appropriate tangible programming language called CHERP, which is specifically designed to program a robot's behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
86
0
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(99 citation statements)
references
References 32 publications
4
86
0
9
Order By: Relevance
“…The children in our study showed interest in the programming activities and exhibited both patience and willingness to follow the teacher's instructions. This is in line with previous research, which found that preschool children often find programming activities attractive and engaging [3] and something they explore in a playful and curious manner [20].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The children in our study showed interest in the programming activities and exhibited both patience and willingness to follow the teacher's instructions. This is in line with previous research, which found that preschool children often find programming activities attractive and engaging [3] and something they explore in a playful and curious manner [20].…”
Section: Discussionsupporting
confidence: 92%
“…When comparing our study with previous research, the studies by Levy and Mouser [19] and Sullivan et al [20] share similar designs. These studies can hence be used as a basis for discussing our results and our study can also to some extent be seen as a replication of their studies.…”
Section: Study Context and Designsupporting
confidence: 77%
See 2 more Smart Citations
“…The studies paid attention to the extent to which young children-including preschool and kindergarten children-were able to learn [31,[49][50][51][52][53][54][55][56]. Bers and her colleagues are key scholars in this area.…”
Section: Effects Of Robotics Education On Young Children's Learningmentioning
confidence: 99%